A Within-Person Approach to Work Behavior and Performance: Concurrent and Lagged Citizenship-Counterproductivity Associations, and Dynamic Relationships with Affect and Overall Job Performance - Dalal, Reeshad s.; Lam, Holly; Weiss, Howard M.; Welch, Eric R.; Hulin, Charles L. (Academy of Management Journal, 2009)
The present research examines the within-person structure of job performance, with an emphasis on the relationship between organizational citizenship behavior (OCB) and counterproductive work behavior (CWB). We demonstrate, via two experience-sampling studies, that OCB and CWB are affect-driven phenomena that exhibit considerable within-person variation. Furthermore, as predicted, the within-person affective forces on OCB were independent of those on CWB—and the two phenomena were themselves independent. When directed at an organization (rather than a supervisor or coworkers), both were, however, related (within-person) to each other and to overall job performance. We discuss implications for the within-person performance structure.